Yorùbá Philosophy and Contemporary Nigerian Realities - Adeshina Afolayan (Yoruba Studies Review)
Beginning from Marx’s understanding of the relationship between philosophy and reality, this Introduction to the special edition of the Yoruba Studies Review explores the inevitable but complex relationship that exists between philosophy and its place. Specifically, it is grounded on the urgency of interrogating Nigeria’s postcolonial realities in the light of Yorùbá philosophical insights that, among other things, enable a rethinking of postcolonial social practices especially as sites of identity, agency, knowledge, objectivity, and even of resistance and power. Premised on the fundamental assumption that Yorùbá philosophy constitutes a fundamental site of scholarship within which the task of understanding and reinventing the Nigerian state and societies can be achieved, the Introduction weaves this assumption into the analysis of the fourteen essays that explores Nigeria’s postcolonial realities ranging from overpopulation, public (im)morality, ethnic conflict, injustice, and democratic deficit to environmental degradation, disability, depersonalization, youth culture, and a glaring disconnection between educational theory and practice.